Edible Bird’s Nest Protects Against Hyperglycemia-Induced Oxidative Stress and Endothelial Dysfunction - Murugan, Dharmani Devi; Md Zain, Zuhaida; Choy, Ker Woon; Zamakshshari, Nor Hisam; Choong, Mel June; Lim, Yang Mooi; Mustafa, Mohd Rais (Frontiers in Pharmacology, 2020)
Increased oxidative stress by hyperglycemia is a major cause of vascular complications in diabetes. Bird's nest, which is made from the saliva of swiftlets has both medicinal and nutritional values dated back to ancient China. However, it’s role in improving endothelial dysfunction due to diabetes is yet to be elucidated. The present study examined the protective effect and mechanism of action of the aqueous extract of hydrolyzed edible bird nest (HBN) on endothelium in models of diabetes, in vitro and in vivo. Male db/m+ and db/db mice were orally administered with or without HBN and glibenclamide for 28 days, followed by vascular reactivity studies in mouse aortas. Human umbilical vein endothelial cells (HUVECs) and isolated mouse aorta from C57BL/6J were treated with high glucose (HG), HBN, sialic acid (SA), glibenclamide and apocynin, respectively. The effects of HBN on reactive oxygen species (ROS) production and nitric oxide (NO) bioavailability were assessed by Western blot, 2',7'-dichlorofluorescin-diacetate (DCF-DA) and 4-amino-5-methylamino-2',7' difluorofluorescein (DAF-FM DA) in HUVECs, isolated mouse aorta and db/db diabetic mice. HBN significantly reversed the endothelial dysfunction in diabetic mice and isolated mouse aorta. HBN normalized ROS over-production of NOX2 and nitrotyrosine, reversed the reduction of anti-oxidant marker, SOD-1 as well as restored NO bioavailability in both HUVECs challenged with HG and in db/db diabetic mice. Similarly, HG-induced elevation of oxidative stress in HUVECs were reversed by SA, glibenclamide and apocynin. This attests that HBN restores endothelial function and protects endothelial cells against oxidative damage induced by HG in HUVECs, isolated mouse aorta and db/db diabetic mice via modulating ROS mechanism, which subsequently increases NO bioavailability. This result demonstrates the potential role of HBN in preserving endothelial function and management of micro- or macrovascular complications in diabetes.